『갈매기의 꿈』: 철학적 갈매기의 비상과 제4부의 재발견, 그리고 텍스트의 재탄생 - 정길화(Gil-Wha Chung) (영미연구, 2022)
『갈매기의 꿈』의 주인공인 조나단에 대한 의인화된 스토리텔링은 그림/사진 이미지들과 함께 각각 지면 속에 나뉘어서 펼쳐지는데, 고통을 수반하는 배움과 성장의 과정에서 자신의 모습이 변모하는 신비한 변신의 모티프를 지니고 있다. 마치 칸트 철학을 자연히 읊조리는 조나단의 대화는 그의 어머니에게 말을 건네는 것으로, 칸트의 첫번째 질문으로 알려진 “나는 무엇을 알 수 있는가?”라는 지적인 것에 대해서이다. 조나단의 철학적 비상은 그가 곧 처하게 되는 실존적 상황으로 인해 기존의 관념에 안주하지 않는 새로운 자아를 찾기 위해 자신을 더욱 전환하게 한다. 조나단의 우화는 현실 안주에서 탈피하고자 하는 자유 의지의 표출이며, 홀로 우주에 던져진 존재로서 21세기 초인 오늘날 환경 위기의 극한 상황을 맞이하여 이를 극복할 수 있는 생태학적 상상력까지 불러일으킬 수 있는 모험 서사이다. 『갈매기의 꿈』은 자아 탐험의 교훈을 전하는 서사로서, 또는 갈매기들의 모험담을 담은 우화로서 시대적 상황에 따라 새롭게 읽을 수 있다. 이 중편소설은 “가장 높이 날으는 갈매기가 가장 멀리 본다”라는 격언이 주제문으로서, 우선 그것이 지닌 절대 최상급의 심층 구조를 이해할 필요가 있다. 본래 영문판에서는 장식문으로 사용하지 않았던 이 격언이 갈매기 한 마리가 나는 그림/사진 이미지와 함께 제1부보다 앞쪽에 사용된 것은 국내 번역판에서만이다. 이는 1973년과 1986년에 각각 새로 출간한 문예출판사의 번역본만의 공통점이다. 2015년 ‘완성본’에 이르러서야 한역 판에서도 이 장식 문장은 제외되었다. 이와 같이 이 논문은 한영판 간의 글과 사진/그림 이미지 간의 구성상 불일치, 제4부의 재발견과 그 효과에 대한 고찰을 포함한다. The personified storytelling of the protagonist Jonathan of Jonathan Livingston Seagull spreads out with its picture/photo images, which has a mystic metamorphosis motif while learning and developing through torture. Jonathan’s dialogue with his mother that seems to narrate the Kantian philosophy is about knowledge well-known with his question, “What can I know?” Jonathan’s philosophical flight is going to confront the existential situation that accelerates his conversion. Jonathan’s fable is an expression of free will to escape from a comfortable life. It is a narrative of adventure about a being deserted in the universe, and today in the early 21st century, it invokes us an ecological imagination of how to confront the extreme state of environmental crisis and how to overcome it. This novella that conveys a lesson of an adventure of selfhood, or contains a fable of adventurous seagulls can be read from new perspectives from the situation of an era. Its topic sentence as a proverb, “The gull sees farthest who flies highest.” has its Absolute Superlative whose deep structure we need to understand. Unlike its original English versions, only those of the Korean translation has its proverb with a picture/photo image, published by Munyechulpansa in 1973 and 1986 per se. In the Complete Korean Edition of 2015, the decorative sentence is finally excluded. This article involves a study on incongruities in its construction between the narrative and picture/photo images, and the rediscovery of Part 4 and its effect. KCI Citation Count: 0